Safety Outcomes of NOTES Cholecystectomy Versus Laparoscopic Cholecystectomy: A Systematic Review and Meta-Analysis. Issue 5 (October 2016) - Peng, Cheng; Ling, Yan; Ma, Chi; Ma, Xiaochun; Fan, Wei; Niu, Weibo; Niu, Jun
Abstract : Objective: Natural orifice transluminal endoscopic surgery (NOTES) is an endoscopic technique whereby surgical interventions can be performed with a flexible endoscope passed through a natural orifice (mouth, vulva, urethra, anus) then through a transluminal opening of the stomach, vagina, bladder, or colon. Although in the early stage of research and development, NOTES has been clinically applied across the globe, above all the transvaginal cholecystectomy is among the most frequently performed procedures. In the existing 2 types of transvaginal routes, the hybrid NOTES cholecystectomy (NC) is more likely to be accepted. However, there has been controversy regarding the safety outcomes of hybrid NC in comparison with classical laparoscopic cholecystectomy (LC). The primary objective of this meta-analysis is to compare the characteristics between NC and classical LC. Materials and Methods: A meta-analysis of eligible studies comparing NC with classical LC was performed to evaluate the safety outcomes including wound complications, other postoperative complications and intraoperative conversion between the 2 groups. Results: Pooling 3 randomized controlled trials (n=157) and 7 nonrandomized trial (n=593) demonstrated that the rates of wound complications and other postoperative complications in NC group did not significantly differ from those of classical LC group [wound complications: ratio difference (RD)=−0.02, 95% confidence interval (CI) −0.04to 0.01, P =0.23; other postoperative complication: RD=−0.01; 95% CI, −0.03 to 0.02; P =0.6]. The intraoperative conversion rate in NC groups was higher than that of LC groups (RD=0.03; 95% CI, 0.01-0.06; P =0.02). Conclusions: There is no significate difference between the safety of NC and laparoscope cholecystectomy. NC is associated with a higher rate of intraoperative conversion when compared with LC. It is worthy of further promotion and validation in clinical settings.